(untitled) (Anais do Salão Inovação, Ensino, Pesquisa e Extensão, 2020)
Pesticides play an important role in combating pests and diseases in the primary sector, increasing productivity and quality of the final product. However, when handled and / or discarded incorrectly, they can cause serious problems for the environment and public health. Graphene-based nanomaterials have unique physical and chemical properties, being not only useful for the detection of pesticides, but also promising tools for the removal of them from the environment. This work consists of a bibliographic review of recent published scientific studies on the use of graphene-derived nanomaterials in the adsorption and removal of pesticides. It was observed that 10 mg of nanocomposites of rGO-Fe3O4 for adsorption and removal of 2 μg / L of triazines in pure water samples, under effect of pH 5, room temperature, contact time of 70 minutes and using acetone as desorption solvent, this can recover up to 93.61% Ametryn, 91,34% Prometryn, 75,24% Atrazine, 88,55% Simazine and 81,22% Simeton. Besides that, 3 mL of graphene in pure water, tap and river water samples, at room temperature, contact time of less than 20 minutes and using 8 mL of acetonitrile as the desorption solvent, the recoveries obtained were of 96,2 and 95,7% for Ametryn, 93,1 and 93,8% for Prometryn, 97,3 and 101% for Prometon, 89,1 and 83% for Atrazine, 94 and 94,6% for Propazine, 87,5 and 87,8% for Cyprazine, 92,9 and 97,3% for Metribuzin, 95,3 and 101,5% for Cyanazine, 94,4 and 95% for Procyazine and 100,5 and 101,6% for Hexazinone, for 0,5 and 5 µg/L of pesticides in pure water. Also, it was used GO-Fe3O4 nanocomposite for adsorption and removal of 2,4-D pesticide in pure water samples. Under effect of pH 3 and using acetone as the desorption solvent, the recovery obtained was of 65,48%. The authors observed that the nanocomposite used for adsorption can be regenerated by acetone and reused for up to 3 times, with adsorption efficiency of 91% at the third time of use. The various derivatives nanomaterial graphene developed and applied by the researchers have well succeeded in adsorption and removal of different pesticides. In this sense, our research group is conducting several tests with different pollutants, and using a new kind of graphene-based material, the three-dimensional graphene forms. The continuity of the present work will study specifically, at molecular level, the interaction of some of these pesticides and different forms of graphene, by fluorescence spectroscopy and theoretical calculations.